Determinants of Micro and Small Enterprise Food Industry Market Expansion in Indonesia - Amzul Rifin (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
One of the indicators that might upgrade micro and small enterprise is the ability to expand their market target outside their location or district. The objective of this article was to analyze the determinants of market expansion for small and medium enterprise especially in the food industry in Indonesia. Market expansion is defined as selling products or services outside the district where the enterprise is located. Secondary data were utilized in the research by using the Micro and Small Enterprise Survey conducted by Statistics Indonesia in 2014 with the data of 21,380 firms. Two analysis were conducted, firstly using the logit analysis in order to differentiate between enterprises selling their products inside and outside the district. The second analysis used Tobit analysis of which the dependent variable is the share of product sold outside the district. Independent variables used in both equations are similar. The results indicated that higher education level, number of labor, value of production, number of enterprise with external finance, number of enterprise located in Java and male-owned firms resulted in higher probability of selling their product outside the district. Moreover, the same variables will also increase the share of product sold outside the district. From the two equations, it can be concluded that the government policy must be addressed in two aspects in order to upgrade the small and medium enterprises, the first is increasing the scale of the enterprises and secondly, fostering financial inclusion for these enterprises.Keywords: micro and small enterprise, logit analysis, tobit analysis, food industry, market expansion